Benchmarking Brain-Computer Interfaces Outside the Laboratory: The Cybathlon 2016 - Novak, Domen; Sigrist, Roland; Gerig, Nicolas J.; Wyss, Dario; Bauer, René; Götz, Ulrich; Riener, Robert (Frontiers in Neuroscience, 2018)
This paper presents a new approach to benchmarking brain-computer interfaces (BCIs) outside the lab. A computer game was created that mimics a real-world application of assistive BCIs, with the main outcome metric being the time needed to complete the game. This approach was used at the Cybathlon 2016, a competition for people with disabilities who use assistive technology to achieve tasks. The paper summarizes the technical challenges of BCIs, describes the design of the benchmarking game, then describes the rules for acceptable hardware, software and inclusion of human pilots in the BCI competition at the Cybathlon. The 11 participating teams, their approaches, and their results at the Cybathlon are presented. Though the benchmarking procedure has some limitations (for instance, we were unable to identify any factors that clearly contribute to BCI performance), it can be successfully used to analyze BCI performance in realistic, less structured conditions. In the future, the parameters of the benchmarking game could be modified to better mimic different applications (e.g. the need to use some commands more frequently than others). Furthermore, the Cybathlon has the potential to showcase such devices to the general public.